Artificial Intelligence and its Effect on Competition and Factor Income Shares - Richard von Maydell (ZBW - Leibniz Information Centre for Economics, 2024)
We examine the impact of self-learning Artificial Intelligence (AI) on firm competition in a growth model with endogenous labor supply and heterogeneous agents. AI possesses the ability to improve autonomously through application, testing, and training. When firms incorporate AI into their production processes, they incur variable costs for acquiring the necessary software as well as fixed costs for installing AI infrastructure. The latter indeed drive productivity increases and economic growth but can also serve as an entry barrier for competing firms. Therefore, we examine how the rise of AI affects market concentration, firm competition, firm productivity and income inequality. We discuss potential policy interventions such as a profit tax or the modernization of competition and merger laws to prevent a significant increase in market concentration and income inequality within AIintensive industries and to foster economic growth.
Keywords: D21; L52; L11; L13; O33; 330; Markups; Artificial Intelligence; Imperfect Competition; Competition Policy; Factor Income Shares